Medical industrial complex visual - Mingus, Mia (Leaving Evidence, 2015)
The following is a visual* of the Medical Industrial Complex (MIC) and is offered as a tool for our work for collective liberation.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capacitisme; cours; discours dominant; eugénisme; fem3300; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; états-unis